(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The literature focuses on studying the financial risks facing the business sector, and rarely focuses on non-financial risks such as legal, operational, and security risks; Therefore, the current study aimed to demonstrate the impact of digital transformation in its dimensions (information technology structure - applications and software - and digital practices) on avoiding non-financial risks in small projects in Riyadh. To achieve this goal, the study was built according to the descriptive analytical approach in its social survey style, and the questionnaire was used as a study tool, which was published in the form of an electronic link on a sample of (384). The SPSS application was also used to analyze the data. The study concluded that there is an effective contribution of digital transformation in avoiding non-financial risks in small projects in Riyadh. In detail, the information network structure does not contribute to avoiding non-financial risks, while there is a positive moral effect and a positive direct relationship for both applications and software, and digital practices in avoiding non-financial risks. The study also presented many recommendations, most notably, continuing to keep pace with modern developments in the field of digital transformation, and training workers on the mechanism of benefiting from technology in detecting, predicting and addressing non-financial risks.